2015
DOI: 10.1007/112_2015_24
|View full text |Cite
|
Sign up to set email alerts
|

The Secretion and Action of Brush Border Enzymes in the Mammalian Small Intestine

Abstract: Microvilli are conventionally regarded as an extension of the small intestinal absorptive surface, but they are also, as latterly discovered, a launching pad for brush border digestive enzymes. Recent work has demonstrated that motor elements of the microvillus cytoskeleton operate to displace the apical membrane toward the apex of the microvillus, where it vesiculates and is shed into the periapical space. Catalytically active brush border digestive enzymes remain incorporated within the membranes of these ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 293 publications
3
57
0
Order By: Relevance
“…The results demonstrated that NCoR1 deletion accelerated cell proliferation and promoted epithelial cell migration in ΔIEC UN mice. Sucrase isomaltase (Sis), a brush border glucosidase, only exists in differentiated duodenal and jejunal enterocytes and has been used as a marker of enterocyte maturation (36,37). Sis gene expression along the CVA was up-regulated in ΔIEC UN mice (Fig.…”
Section: Developmental Stage-dependent Derepression Of Ugt1a1 Expressionmentioning
confidence: 99%
“…The results demonstrated that NCoR1 deletion accelerated cell proliferation and promoted epithelial cell migration in ΔIEC UN mice. Sucrase isomaltase (Sis), a brush border glucosidase, only exists in differentiated duodenal and jejunal enterocytes and has been used as a marker of enterocyte maturation (36,37). Sis gene expression along the CVA was up-regulated in ΔIEC UN mice (Fig.…”
Section: Developmental Stage-dependent Derepression Of Ugt1a1 Expressionmentioning
confidence: 99%
“…While hCPA1 and hCPA2 show a higher preference for small aliphatic and bulky aromatic side chains, respectively (14), hCPB preferentially cleaves substrates with C-t basic amino acids (15)(16)(17). Although their combined action can release a wide range of amino acids that are absorbed in the intestinal tract, pancreatic MCPs are unable to release acidic C-t amino acids, such as Asp or Glu (13,18,19), even though these acidic residues are two of the most abundant amino acids in alimentary proteins (20)(21)(22).…”
mentioning
confidence: 99%
“…44,45 In this sense, mucosal maltase-glucoamylase and sucrase-isomaltase complexes could hydrolyze to α(1 → 6) bonds between the monomers of both AlphaGOS P and melibiose. 20,21,46 These enzymatic structures could also have more versatility in terms of hydrolytic activity, as was showed elsewhere. 16,47 To the best of our knowledge, these data are the first evidence about digestibility of α-GOS with small intestine enzymes.…”
Section: Digestion Of Prebiotic Carbohydrates Using Rsiementioning
confidence: 57%
“…20 Sucrase site splits glucose and fructose, while isomaltase site splits Glc-Glc α(1 → 4) and α(1 → 6) linkages, being one of the most common complexes in the small intestine. 21 Inulinase activity showed the lowest value, which could be related to the low digestibility of prebiotic fructans. 14,22…”
Section: Enzymatic Characterization Of Rsiementioning
confidence: 95%